1988
DOI: 10.1111/j.1476-5381.1988.tb11608.x
|View full text |Cite
|
Sign up to set email alerts
|

The affinity of some acetylenic analogues of 4‐DAMP methobromide for muscarinic receptors in guinea‐pig ileum and atria

Abstract: 1 The replacement of 4-hydroxy-N-methyl piperidine (HO NMe) in 4-diphenylacetoxy-Nmethyl piperidine (4-DAMP) metho-bromide by 4-hydroxy-but-2-ynylamines (HOCH2C= CCH2NR2) reduces the affinity for muscarine-sensitive acetylcholine receptors in guinea-pig ileum and atria. It does not abolish selectivity. The tertiary amines are more active and more selective than the corresponding quaternary salts. 2 Analogous derivatives of 4-hydroxy-but-2-ynylamines which lack the ester group (i.e. substituted 4-hydroxymethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Increasing the size of the onium group from dimethylamino to pyrrolidino, however, reduces affinity. This is similar to what is seen with the corresponding butynes (Barlow et al, 1988) but unlike what is observed with choline derivatives (Abramson et al, 1969). These compounds all have much less affinity than 4-DAMP methobromide.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Increasing the size of the onium group from dimethylamino to pyrrolidino, however, reduces affinity. This is similar to what is seen with the corresponding butynes (Barlow et al, 1988) but unlike what is observed with choline derivatives (Abramson et al, 1969). These compounds all have much less affinity than 4-DAMP methobromide.…”
Section: Resultssupporting
confidence: 84%
“…The very high selectivity of p-fluorohexahydro-sila-diphenidol can also be seen but the compound has relatively low affinity, less than that of silabenzhexol or silaprocyclidine (Barlow & Shepherd, 1986). The value for receptors in ileum (log K = 7.6) is comparable with that of diphenylhydroxymethyl-prop-3-ynyl-trimethyl-ammonium (log K = 7.3;Barlow et al, 1988), which has a C-CC-C chain instead of Si-C-C-C, but this compound has no selectivity (for atria log K = 7.4).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The atria were set up as described by Edinburgh Staff (1974) in Krebs solution containing norphenylephrine (5 gM: Barlow & Shephard, 1986;Barlow et al, 1988), aerated with a mixture of oxygen (95%) and carbon dioxide (5%). The volume of the bath was about 21 ml and the contractions were recorded isotonically with a load of about 0.5 g. The temperature was 30'C.…”
Section: Guinea-pig Isolated Atriamentioning
confidence: 99%